INFORMATION TECHNOLOGY GOVERNANCE PROCESS MATURITY IN HIGHER EDUCATION INSTITUTIONS IN SOUTH AFRICA - Johl, Christian; Flowerday, Stephen; Von Solms, Rossouw (South African Journal of Higher Education, 2016)
The Department of Education, South Africa, published a white paper on the transformation of the higher education sector in 1997, to ensure that the sector would meet the criteria for the higher education agenda of the country. Governance of the higher education sector in South Africa is defined in an Act of parliament governing the sector, Act 101 of 1997, as amended. The Act defines the governance organs required. Whilst the corporate governance requirements are well defined and practiced, there is no formal requirement for the governance of information technology (IT). This paper investigates the maturity levels of IT governance processes in public higher education institutions in South Africa, using the COBIT 4.1 framework developed by the Information Systems Audit and Control Association (ISACA). Ten of the twenty-three public higher education institutions in South Africa participated in a survey requiring 78 responses each. The empirical results of this survey on the level of IT governance process maturity will be presented and discussed to better understand the factors contributing to IT governance process maturity levels in the public higher education sector in South Africa.